The relationship of individual comorbid chronic conditions to diabetes care quality. Issue 1 (23rd July 2015) - Magnan, Elizabeth M; Palta, Mari; Mahoney, Jane E; Pandhi, Nancy; Bolt, Daniel M; Fink, Jennifer; Greenlee, Robert T; Smith, Maureen A
Abstract : Objective: Multimorbidity affects 26 million persons with diabetes, and care for comorbid chronic conditions may impact diabetes care quality. The aim of this study was to determine which chronic conditions were related to lack of achievement or achievement of diabetes care quality goals to determine potential targets for future interventions. Research design and methods: This is an exploratory retrospective analysis of electronic health record data for 23 430 adults, aged 18–75, with diabetes who were seen at seven Midwestern US health systems. The main outcome measures were achievement of six diabetes quality metrics in the reporting year, 2011 (glycated haemoglobin (HbA1c) control and testing, low-density lipoprotein control and testing, blood pressure control, kidney testing). Explanatory variables were 62 chronic condition indicators. Analyses were adjusted for baseline patient sociodemographic and healthcare utilization factors. Results: The 62 chronic conditions varied in their relationships to diabetes care goal achievement for specific care goals. Congestive heart failure was related to lack of achievement of cholesterol management goals. Obesity was related to lack of HbA1c and BP control. Mental health conditions were related to both lack of achievement and achievement of different care goals. Three conditions were related to lack of cholesterol testing, including congestive heart failure and substance-use disorders. Of 17 conditions related to achieving control goals, 16 were related to achieving HbA1c control. One-half of the comorbid conditions did not predict diabetes care quality. Conclusions: Future interventions could target patients at risk for not achieving diabetes care for specific care goals based on their individual comorbidities.